A novel and efficient instrumentation technique for human blood pressure measurement using computational intelligence method. (2018) - Isaac, J. Samson; Porkumaran, K.
Blood pressure is one of the vital parameters in the evaluation of cardiovascular function and status. Moreover, continuous measurement and regulation of blood pressure exhibits a challenge in clinical settings. A novel and efficient instrumentation system for the continuous measurement of human blood pressure using the photoplethysmogram signal has been developed based on computational intelligence techniques using LabVIEW software tool. The system indicates the systolic and diastolic blood pressures accurately when calibrated against gold standard and shown in Clarke's error grid. The results were better among the population participated in the age groups between 50 and 75 and body mass index ranging from 19 to 28.